PREDICTION OF VEGETABLE SUPPLY CRISIS TO URBAN AREAS WITH CONCEPT OF CRISIS BAROMETERS, BETA DISTRIBUTION, ESTIMATION OF THE POSSIBILITY VALUE AND MARKOV CHAINS - Erna Rusliana M. Saleh dan Taufik Djatna (Department of Agroindustrial Technology, Bogor Agricultural University, 2011)
ABSTRACT Vegetable is a perishable commodity. When the crisis occurred such as floods, damages suffered by the company supplying the vegetables will be even greater, since the supply process is stuck. Floods in DKI Jakarta in recent years caused economic activity, including any system of vegetable supplies in crisis. Therefore, efforts are needed to deal with strategic planning the distribution of vegetables. The purpose of this paper was to identify the crisis conditions, to estimate the timing of the crisis and to predict the likely location of the crisis affected the supply of vegetables to urban areas due to flooding occurred with the concept of crisis barometer, the beta distribution, the estimated value of the possibility and markov chain. The results of the aggregation values of CIV and PF for forecasting the condition of vegetable supplier corporate crisis, obtained a value of 8 and 71.7% of the mean position of the status of the crisis faced by the firm was in alarming condition. Estimated time of vegetable supply crisis was expected to occur in 1126 years later. Predicted results show the possible locations of crisis that the possibility of crisis events in Jatinegara, Pulogadung, Kramat Jati, Cakung, Makassar, Pasar Rebo, Ciracas, Matraman and Duren Sawit for 2012 were 18.93%, 8.80%, 14.63%, 20.61%, 8.69%, 4.89%, 12.93%, 2.57%, and 8.98%. Keywords: vegetable supply, crisis prediction, crisis barometer, beta distribution, estimate the value of possibility, markov chains